Effects of n-butanol fraction of Gongronema latifolium leave extract on some kidney function and histological parameters in CCl4-induced oxidative damage in Wistar albino rats. - J.C., Okpala; H.N., Ifedilichukwu (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Effects of n-butanol fraction of Gongronema latifolium leave extract on some kidney function and histological parameters in (CCl4) carbon tetrachloride-induced oxidative damage in Wistar albino rats were assessed. Fifty-four (54) Wistar albino rats were divided into treatment and LD50 groups. The treatment group was further divided into seven groups of 6 animals each by the randomized random design method, each were allowed food and water ad libidium. Group A (normal control) was given feed and water, Group B (vehicle control) was injected with olive oil intraperitoneally, while the rest groups (C, D, E, F and G) were injected intraperitoneally with a single dose of CCl4 (148 mg/kg) at 1:1 (v/v) solution in olive oil and all the animals were fasted for 36 hours. This was repeated once every week for a period of four (4) weeks. At the end of 28 days of treatment, there was significant (p<0.05) reduction in weight change of CCl4-induced control rats when compared with the normal control and induced treated groups. Kidney function studies showed that there was significant (p<0.05) increase in creatinine and urea levels of CCl4-induced control group when compared with the normal control and induced treated groups but there was no significant (p>0.05) difference between the normal control and induced treated groups. Also, the kidney homogenate revealed significant (p<0.05) decrease in superoxide dismutase, catalase and glutathione peroxidase activities in CCl4-induced control rats when compared with the normal control rats but there was no significant (p>0.05) difference between the normal control and induced treated groups. However, malondialdehyde concentration was significantly (p<0.05) higher in CCl4-induced control rats when compared with the normal control and induced treated rats. These findings suggested that n-butanol fraction of methanolic leave extract of G. latifolium may have anti-nephrotoxic and antioxidative effects against CCl4-induced kidney damage in rats.